2021
DOI: 10.4103/ijds.ijds_231_20
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Evaluation of Reliability of Cephalometric Analysis of Cephalometrically Diagnosed Skeletal Class I Malocclusion using Readily Available Digital Imaging Software such as IMAGE J and ICY and Traditional Manual Tracing

Abstract: Background: The skeletal and soft tissue analysis of the face in total is a very important parameter of diagnosis. Readily available and non expensive imaging software are available which can be used for cephalometric analysis for hard and soft tissues of the face to make an appropriate treatment plan. Aims: The purpose of this study was to compare the accuracy of linear and angular measurements between the digital software IMAGE J, ICY and manual traci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The values of SNA, SNB and ANB was found significant due to problem in identification of point nasion and point A. Albarkati et al 15 and Gregston et al 5 have also reported significant value of SNA and SNB. Contrary to this finding Ganna et al, 19 Mahto et al 3 and Khan et al 27 found non-significant value of SNA and SNB. Santoro et al 26 also found significant value of ANB due to difficulty in identification of landmarks like point A and nasion but contrary to this, Izgi et al 22 and Mahto et al 3 found non-significant value of ANB.…”
Section: Discussionmentioning
confidence: 78%
“…The values of SNA, SNB and ANB was found significant due to problem in identification of point nasion and point A. Albarkati et al 15 and Gregston et al 5 have also reported significant value of SNA and SNB. Contrary to this finding Ganna et al, 19 Mahto et al 3 and Khan et al 27 found non-significant value of SNA and SNB. Santoro et al 26 also found significant value of ANB due to difficulty in identification of landmarks like point A and nasion but contrary to this, Izgi et al 22 and Mahto et al 3 found non-significant value of ANB.…”
Section: Discussionmentioning
confidence: 78%